Treatment of wrist and hand fractures with natural magnets: preliminary report - Costantino, C.; Pogliacomi, F.; Passera, et al., F. (Acta Biomedica Atenei Parmensis, 2007)
The Authors, after having defined the phenomenon and the biological characteristics of natural magnets, evaluate their ability in accelerating the formation of bone callus in hand and wrist fractures compared to treatment with immobilization in a plaster cast. Forty patients (4 females and 37 males) between 20 and 86 years of age were treated. A small natural magnet was inserted in each of the plaster casts (diameter: 2cm, height: 0.5cm) made of 4 blocks in Neodymium-Iron-Boron, capable of generating 4 magnetic poles (2 positive and 2 negative) of diagonal alternate polarity that produced a symmetric, quadruple static magnetic field. The created magnetic flow was wavelike, concentrated in one direction, and developed a force up to 12,500 gauss. From this study it has emerged that inserting a quadruple magnet in a plaster cast in hand and wrist fractures results in the formation of bone callus in an average time that is 35% inferior to the “standard” time. Accelerating the healing of the fracture is important since it reduces immobilization time for the joints involved, avoiding subsequent weakness and stiffness and allowing the patient to begin rehabilitative physiotherapy sooner, which permits a faster functional recovery.